Features of the updated curricula and improvement of the educational process - Mikhailova, N.B.; Baimukhanova, M.T.; Pazylbek, B.K. (KSU publ., 2020)
The article discusses the features of the updated education system of the Republic of Kazakhstan. The authors drew attention to the fact that the updated educational program introduced in the sphere of education of the Republic of Kazakhstan is a new program that meets the needs of future generations, meets modern requirements.The article deals with the issue of the teacher's development of innovative technologies in modern conditions of education and the objective necessity of their application in teaching children in their lessons. The relevance of innovative learning according to the authors ' research is the use of personalityoriented learning, as well as the creation of conditions for the disclosure of the creative potential of students. The main goal of education in the modern world — prepare professional, competitive, competent, knows his job in the labour market-oriented direction, able to work effectively at the level of world standards, to grow professionally, to respond effectively to the socio-political processes, adapt quickly to change, able to solve industrial-innovative situation, to Express themselves in accordance with their needs and the needs of society, to freely Express their thoughts, to have a high knowledge of the national language, history, to form domestic and world culture. The article describes that the evaluation system undergoes radical changes and moves to the system of criterion evaluation.
Keywords: updated education system; criteria-based assessment; innovative education; information technologies